Recherche participative efficace entre paysans, ONG, SNRA et IITA pour controler Striga hermonthica au Nord du Benin - Versteeg, M.; Adanguidi, J.; Djenotin, J.; Nonfon, R. (1994)
This library research report will be particularly useful to French-speaking research workers in agriculture who want to get information about the Participatory Rural Appraisal (PRA). A synthesis is written from several documents and from a questionnaire which has been send to ex-alumni of the French International Course for Development oriented Research in Agriculture (ICRA, Montpellier, France).